2010
DOI: 10.1016/j.jacc.2009.08.091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High-Dose N-Acetylcysteine Versus Placebo on Contrast-Induced Nephropathy and Myocardial Reperfusion Injury in Unselected Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: High-dose intravenous N-acetylcysteine reduces oxidative stress. However, it does not provide an additional clinical benefit to placebo with respect to CIN and myocardial reperfusion injury in nonselected patients undergoing angioplasty with moderate doses of contrast medium and optimal hydration. (Myocardial Salvage and Contrast Dye Induced Nephropathy Reduction by N-Acetylcysteine [LIPSIA-N-ACC]; NCT00463749).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
121
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(129 citation statements)
references
References 33 publications
5
121
0
2
Order By: Relevance
“…The volume of low-osmolar contrast agent administered (173 ± 42 mL) was lower than in older relevant trials or similar to recent trials [3,9,10]. MACD was exceeded in 3% of patients only.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The volume of low-osmolar contrast agent administered (173 ± 42 mL) was lower than in older relevant trials or similar to recent trials [3,9,10]. MACD was exceeded in 3% of patients only.…”
Section: Discussionsupporting
confidence: 58%
“…STEMI patients treated by primary PCI represent a population at higher risk for AKI than those undergoing elective coronary angiography and/or PCI. Renal hypoperfusion caused by HF or prolonged hypotension, larger volume of contrast media, bleeding, and atheroembolic events during catheterisation are the most cited conditions that contribute to renal injury [3,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this notion, NAC as an exogenous thiol-providing ROS scavenger did not alter the functional state of postischemic Txnrd2ϩ/-control mice in our model. Consistently, in a recent clinical study, 49 NAC (2 x 1200 mg/d) did not increase the myocardial salvage of patients with ST elevation myocardial infarction, bona fide Txnrd2 carriers. Only in the instance of Txnrd2 deficiency did thiol supplementation by NAC attenuate I/R injury, enabling a functional improvement to the level of Txnrd2ϩ/-control mice ( Figure 6A and 6B).…”
Section: Discussionsupporting
confidence: 73%
“…A large number of drugs have been used to protect renal function after PCI, such as aminophylline (Shammas et al 2001;Rohani 2010), theophylline (Wang et al 2001), atrial natriuretic peptide (Chen 2009;Morikawa et al 2009), B-type natriuretic peptide (Zhang et al 2010), mannitol (Kelly et al 2008), prostaglandins (McCullough andTumlin 2009), N-acetylcysteine (Thiele et al 2010), sodium bicarbonate (Masuda 2008) and statins (Xinwei et al 2009); however, few of them (Kowalczyk et al 2007;Zoungas et al 2009) have shown exact protective effects.…”
Section: Discussionmentioning
confidence: 99%